2021
DOI: 10.1039/d0en00983k
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids improve bacterial tolerance towards biobutanol through membrane stabilization

Abstract: The nano-aggregation of carotenoids in microbial membranes increases membrane stability upon butanol exposure by reducing the fluidization effect and membrane permeability of butanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
(101 reference statements)
0
6
0
Order By: Relevance
“…The disruption of membrane integrity and the increase of membrane fluidity were also observed and assumed to be crucial factors in determining butanol toxicity. Subsequent experimental methods 223 confirmed that carotenoids could reduce butanol penetration and membrane fluidization effect by fortifying cell membranes and thus improve butanol tolerance in E. coli.…”
Section: Effects Of Small Organic Molecules On Membranesmentioning
confidence: 96%
“…The disruption of membrane integrity and the increase of membrane fluidity were also observed and assumed to be crucial factors in determining butanol toxicity. Subsequent experimental methods 223 confirmed that carotenoids could reduce butanol penetration and membrane fluidization effect by fortifying cell membranes and thus improve butanol tolerance in E. coli.…”
Section: Effects Of Small Organic Molecules On Membranesmentioning
confidence: 96%
“…They present significant biological properties, for example, acting as antioxidants and protecting cells and tissues from the harmful effects of free radicals and singlet oxygen [ 55 ]. In addition, these compounds were reported to engage in photoprotection, and membrane stabilization [ 56 , 57 , 58 ]. Certain studies report that carotenoids possibly lowered the phase transition temperature of synthetic lipids and worked as regulators for membrane fluidity since they showed an important role in the causative function in the modulation of membrane parameters [ 59 , 60 ].…”
Section: Significance Of Arthrobacter Spp In the D...mentioning
confidence: 99%
“…The authors suggest using carotene-rich waste (e.g. tomato pomace) as a cheap carbon and carotene source, making this approach even more interesting for the sustainable production of chemicals [ 58 ].…”
Section: (Semi-) Rational Approachesmentioning
confidence: 99%